The patterning of obsessive love in Lolita and Possessed (2017)
ABSTRACT: Nabokov’s work is well known for its complexity and its convoluted plots, something which is particularly true of Lolita, which is rich in patterns, repetitions and mises en abyme. The latter take the form of intertextual relations, references to painting, popular culture or cinema (and, in fact, Nabokov’s relation to the cinema has been the subject of many papers and books). Two films are mentioned in the novel: Possessed and Brute Force. In what follows, a comparison will be made between the former and the novel in terms of the repetition of the obsessive love present in both works. Humbert and Louise are obsessive lovers and their obsessions paradoxically lead them to develop aggressive feelings towards the beloved—to the point of physical violence or at least the phantasy of it. Those obsessions are also a manifestation of their mental instability, something which makes them extremely unreliable narrators in a context of a confession they make, resulting in the text we read or the film we see. While Humbert explains and justifies his acts in his confession, however, Louise is made to talk to a psychiatrist. The purpose of this analysis is to find common patterns in the novel and the film in the terms of obsessive love, hostility towards the beloved, madness, unreliable narration and confession.